POLITIK HUKUM DAN SISTEM PEMBANGUNAN HUKUM PIDANA INDONESIA - Indra Ariska, Dudung; Arifin, Jajang (Yustitia, 2017)
The development of Indonesian law is an actualization of the existence of a state of law (the Rule of Law) and also it is an effort to build a quality of Indonesian people, where development of this law will not be separated from the role of political law that gives the direction of our legal system will run. Development should not ignore changes of law in the structure of society and the changing times. Therefore a good law is a law that can respond to the needs of society, therefore the law can also be referred to as a means of social engineering (law as a tool of social engineering) In the implementation of the formation of draft laws to be made, not only should observe the policies of the law, will but it is also very important to note in this case forming elements of a draft law, which the constituent elements are matters relating to the principles of both the formal principle that is the form of the draft legislation and the principles of materiel concerning the content or substance of the bill and then the foundations up to the charge of material that will be described in the draft legislation. Thus benefit from the establishment of these laws can be felt by the entire people of Indonesia, also in this case do not ignore this aspect of the rule of law itself, which is a function of the formation of a statute.